Biomechanics and bone (& II): Trials in different hierarchical levels of bone and alternative tools for the determination of bone strength. - Caeiro, J. R.; González, P.; Guede, D. (Journal of Osteoporosis & Mineral Metabolism / Revista de Osteoporosis y Metabolismo Mineral (Spanish edition))
For a greater understanding of the mechanical properties of bone as a whole, it is first necessary to determine the behaviour of each of the components in an individual way at its corresponding structural level, as well as its overall involvement. This is the basis of the theory of hierarchical structure of bone, which involves its division into different structural levels. In this work we review, level by level, this hierarchical structure, reviewing the different mechanical trials which are applied to each of the structure. In addition, the methods for the determination of bone strength alternative to the classic mechanical trials are presented, which in recent years have been contributing significantly to the mechanical understanding of bone.